Exploring teachers' perceptions of their pedagogical role with computers: a case study in Malaysia - Wong, Su Luan; Atan, Hanafi; Sabudin, Shahril (Elsevier, 2010)
This study explores teachers’ perceptions of their pedagogical role when conducting science laboratory sessions with computers. Participants in this study were science teachers from 42 randomly selected secondary schools in the state of Negeri Sembilan, Malaysia. The data from 209 teachers (148 females and 61 males) were used for data analysis. There were twelve items in the questionnaire, six items related to the student-centred pedagogical role while the other six related to the teacher-centred pedagogical role. The findings of the study suggest that teachers perceive their pedagogical role as being more student-centred in the science laboratories. Although the results of this study indicate that teachers have assumed the student-centred pedagogical role, they also suggest that teachers are only moderately ready to use this approach in their instruction of science laboratory sessions when computers are available.